Metodologías activas para el desarrollo de la comprensión lectora en los estudiantes del primer año de bachillerato de la Unidad Educativa Prof. Manuel del Pino del cantón Cumandá, provincia de Chimborazo en el período académico 2021 - Naranjo Brito, Anabel Lisbeth (2022)
Reading comprehension is that which, through the individual's previous experiences. It allows to understand a text and gives the facility to decode written texts. In this environment, the present research was a suggestion as a primary purpose for the teachers of the Educational Unit Prof. "Manuel del Pino" the active methodologies for the strengthening of reading comprehension of the students of the first year of high school of the Educational Unit Prof. Manuel del Pino of the Cumandá canton, province of Chimborazo in the academic period 2021. This detailed study had a quantitative approach and was developed with a population of fifteen students. After describing the active methodology theoretically, collected data through a survey developed in Google Forms to know their perceptions regarding reading comprehension and teaching skills related to implementing positive methods. To understand the students' level of reading comprehension, the students were evaluated with a pre-test. It was possible to know and interpret the data collected, and it was verified their low degree of reading comprehension, after the application of active methodologies, an improvement was obtained, which was verified through a post-test.